Female Annual Killifish Austrolebias reicherti (Cyprinodontiformes, Rivulidae) Attend to Male Chemical Cues. (13th August 2013) - Passos, Carlos; Reyes, Federico; Tassino, Bettina; Rosenthal, Gil G.; González, Andrés
Abstract: Chemical communication is an important mediator of social interactions in fish, including mate recognition, mate choice and intrasexual competition. We used a simultaneous‐choice design to test the response of adult females of the annual killifish, Austrolebias reicherti, towards male‐conditioned water, both crude and fractionated into its polar and non‐polar components. Females preferred male‐conditioned water when tested both against control water and female‐conditioned water. The polar and non‐polar fractions of the male‐conditioned water were not significantly attractive, although a tendency was observed towards the non‐polar fraction. Our study shows that annual fish respond to the chemical cues of potential mates. The chemical channel is likely to be particularly important in the muddy ephemeral ponds in which they occur.